2015
DOI: 10.5815/ijieeb.2015.06.02
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Attribute Decision Making Using Simple Additive Weighting and Weighted Product in Food Choice

Abstract: Abstract-This paper provide an overview of the analysis and implementation Multi-Attribute Decision Making (MADM) for food selection or food choice. Food choice aim to find the solution on lack of food. Food choice can be doing with diversification. Food diversification aims to find best choice of food alternatives. Food alternative is rice, corn, cassava, potato, sago, sorghum, wheat, and analog rice. The method used is Simple Additive Weighting (SAW) and Weighted Product (WP). The use of this method is expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 7 publications
0
8
0
2
Order By: Relevance
“…Multi-Attribute Decision-Making (MADM) is used for situational, analytical, and synthetical components, with aggregation and alternative ranking for information processing. The MADM Model is done by evaluating the alternative Ai (i = 1,2, ..., m) for a set of attributes or Cj criteria (j = 1,2, ..., n), the weighting factor Wj on the decision matrix of each alternative for each attribute X with formula based on paper [15].…”
Section: Madmmentioning
confidence: 99%
“…Multi-Attribute Decision-Making (MADM) is used for situational, analytical, and synthetical components, with aggregation and alternative ranking for information processing. The MADM Model is done by evaluating the alternative Ai (i = 1,2, ..., m) for a set of attributes or Cj criteria (j = 1,2, ..., n), the weighting factor Wj on the decision matrix of each alternative for each attribute X with formula based on paper [15].…”
Section: Madmmentioning
confidence: 99%
“…Berdasarkan penjelasan ketiga penelitian diatas dapat disimpulkan bahwa metode SAW penentuan nilai bobot subkriteria menggunakan penerapan Fuzzy Logic dalam mentransformasikan entitas nya serta angka persen dalam mentransformasikan bobot kriteria [11]. Berikut langkah penyelesaian SAW [12]:…”
Section: Pendahuluanunclassified
“…7) Additional required information: some MCDM methods need additional information to get the better result. [ [168][169][170][171][172][173] IV. CONCLUSIONS Decision Making is an essential technique and it is found that the application of these techniques are increasing.…”
Section: ) Incomparable Optionsmentioning
confidence: 99%